Strategi Komunikasi Media Sosial untuk Mendorong Partisipasi Khalayak pada Situs Online kitabisa.com - Herna Herna; Hiswanti Hiswanti; Hidayaturahmi Hidayaturahmi; Amanda Anindya Putri (Institut Pertanian Bogor, 2019)
The development and widespread use of internet technology has changed the way people communicate in everyday life. The most important indicator of this transformation is the emergence of new communication devices with internet technology called